Soil Characterization In Ex-Manganese Mining Land In North-Central Timor District, East Nusa Tenggara - Tobing, Wilda Lumban Tobing; Magdalena Kolo, Maria; Bria, Deseriana; Putra Purba, Mahardika; Maria Paulo Soares, Efieno (International Journal of Science, Technology & Management, 2022)
Manganese (Mn) mining in North Central Timor results in open land conditions that can change soil qualities. The aim of this study was to determine physical characteristics and chemical properties of the soil in the ex-manganese mining areas. The study was performed from June – September 2021. Soil characterization was carried out at selected locations where manganese mining was carried out both traditionally and using technology. The soil characteristics measured were texture, water content, bulk density, mass density, porosity, organic matter content, pH, cation exchange capacity (CEC), organic C, total nitrogen (N), total phosphorus (P), total potassium (K), and total Mn. The results showed that the physical characteristics of the soil on ex-Mn mining land from 5 villages in TTU, NTT are dominated by sand texture which results in low water content (3.39 - 9.46 %), soil porosity (14.96 - 59.31 %), and high bulk density (1.18 - 1.49 g cm-3). Characteristics of soil chemical properties showed low pH (< 7), organic matter (0.06 – 0.81%), organic C (0.03 – 0.22 %), total N contents (0.05 – 0.22%), and high total P (14.77 – 61.44 me 100 g-), K (66.66 – 71.18 me 100 g-), and Mn (18.802 – 24.055 ppm) contents. Land must be reclaimed Reclamation can be done by land management, top soil conservation, planting pioneer crops or cover crops.